Anorexia en estudiantes de la Unidad Educativa Fray Álvaro valladares de la ciudad de Puyo, Pastaza. año 2015 - Carvajal Vallejo, Beatriz Elizabeth (2016)
The research studied the incidence of practices harmful to health arising anorexia among students in the educational unit Fray Alvaro Valladares city of Puyo, caused by the large amount of publicity in the media perceived to be beautiful is means to be thin. The study determined the incidence and factors associated with anorexia. The research had the following design: transversal, descriptive literature, quantitative and fixed field. The survey was applied to 135 students in seventh, eighth, ninth and tenth years was used as a technique. The results of this research showed was that 38.51% of students have harmful practice of feeding behavior by determining the incidence of anorexia was 2.96%. Of all the people that involves the study 67.31% are between the age of 12-14 years in one are ethnic mixed in 96.16% and 71.15% from urban belong to families of middle level high 76.92%. The main predisposing factors are the absence of parents for work at meal times; Mother at 57.70% and the absence of fathers in 76.92%; students are aware that anorexia and is practiced in 2.96%. The 44.23% reported anemia as the main effect. It was concluded that there is a high percentage of young people at risk and incidence of anorexia is of 2.96%. Adolescents are vulnerable to society as the main causal found in the study is the lack of presence and vigilance of parents in hours of eating what triggers this eating disorder and confusion in them using these methods. Keywords:Anorexia,Student,educational unit